Unlocking the Potential of Technology in Nursing Skills Education: A Randomized Controlled Trial. - GÖÇMEN BAYKARA, Zehra; ÇALIŞKAN, Nurcan; ÖZTÜRK, Deniz; KARADAĞ, Ayişe; SARITAŞ, Evrim; EYÜBOĞLU, Gülcan; AYDOĞAN, Sinan; DOĞAN, Nevin; GÜNDÜZ, Ceyda Su (Journal of Nursology, 2025)
Objective: This study aimed to determine the effect of illustrated checklists and web-access videos on nursing students' basic nursing knowledge levels and psychomotor skills. Methods: This single-blind, randomized controlled trial was conducted with 205 first-year nursing students registered in a Fundamentals of Nursing course. The students were stratified by gender and randomly assigned to the experimental and control groups using simple randomization. All students participated in theoretical lectures, demonstrations, and laboratory practices. The Intervention Group's laboratory practices were supported by illustrated checklists and web-access skill videos. Results: The intervention group's objective structured clinical exams and knowledge test scores were significantly higher than the control group's (P < .05). In total, 95.4% of the students stated that watching videos facilitated learning. Conclusion: The study found that illustrated checklists and web-accessible skill videos improved students' knowledge and skills and that the skill videos facilitated learning, increased motivation, and enhanced clinical preparation. The widespread use of illustrated checklists and web-access skill videos in nursing skills education is suggested.